The Effect of Brexit on British Workers Living in the EU - Ana Venâncio; Jo\~ao Pereira dos Santos (Center for Economic Studies and ifo Institute (CESifo), 2022)
The effect of Brexit is an important topic in the European and British political agendas. This study examines the perspective of the EU countries, with regards how British citizens working in an EU country reacted to the end of free movement of workers. Employing synthetic control methods and using data from Portugal, we estimate how the behaviour of UK citizens working in Portugal would have evolved if the Remain vote had won the referendum. Our results suggest that the Brexit referendum reduced the number of UK citizens working in Portugal, particularly in the case of non-university educated, male individuals with temporary employment contracts. This reduction is explained by the decrease in the number of incomers. We also find that those UK citizens who were already working in Portugal before Brexit are less likely to leave the country.
Keywords: J10; J61; J68; 330; Brexit; employment; migration